Taxonomic and nomenclatural notes on Sorbus foliolosa and related taxa (Rosaceae) - Chen, Xin (Phytotaxa, 2018)
Taxonomic status of Sorbus foliolosa, Pyrus foliolosa var. ambigua, S. wallichii, S. ursina and S. ursina var. wenzigiana were discussed. Lectotypes designated for S. foliolosa and S. wallichii by Long and for S. ursina by Gabrielian are confirmed. Second-step lectotype of S. ursina var. wenzigiana and lectotype of P. foliolosa var. ambigua are designated here. Sorbus foliolosa, S. wallichii, and S. ursina are recognized. Sorbus ursina var. wenzigiana is reduced to a synonymy of S. foliolosa. A new combination, S. foliolosa var. ambigua is proposed.